2019
DOI: 10.1021/acs.jpcc.9b05844
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Specific Spectroscopy of Water at a Potentiostatically Controlled Supported Graphene Monolayer

Abstract: Knowledge of the structure of interfacial water molecules at electrified solid materials is the first step toward a better understanding of important processes at such surfaces, in, e.g., electrochemistry, atmospheric chemistry, and membrane biophysics. As graphene is an interesting material with multiple potential applications such as in transistors or sensors, we specifically investigate the graphene–water interface. We use sum-frequency generation spectroscopy to investigate the pH- and potential-dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 46 publications
0
34
0
1
Order By: Relevance
“…The graphite–water interface constitutes a prime example for studying the water structure at a seemingly simple model surface. Besides the fundamental interest in elucidating the water structure at a surface that is generally believed to be hydrophobic, the graphite/graphene surface also serves as a model system for many application-related studies. In the past, an ever-growing number of research groups have reported atomic force microscopy (AFM) experiments on the formation of well-ordered stripes on the graphite/graphene surface. Despite their ubiquitous appearance, the origin and many structural details of these stripes are still under debate. For example, the stripes have been reported to order in domains with different orientations with respect to each other. Moreover, different stripe widths ranging from 2 to 6 nm have been reported in literature. ,, Similarly, contradicting information is available on the solvation structure on top of the stripes. , Although some groups have ascribed the stripes to airborne contaminations or to the formation of methanol–water nanostructures, others have explained the origin of the stripes by intercalation and different interplanar stackings or the assembly of dissolved nitrogen molecules at the graphite/graphene–water interface. , The interpretation of the stripes being composed of nitrogen has received considerable attention because of its potential impact for explaining the long-range nature of the hydrophobic interaction. ,, In the view of this discussion, it becomes increasingly relevant to shed light onto the structural details of the stripes and, in particular, to clarify the chemical nature of the constituents.…”
Section: Introductionmentioning
confidence: 99%
“…The graphite–water interface constitutes a prime example for studying the water structure at a seemingly simple model surface. Besides the fundamental interest in elucidating the water structure at a surface that is generally believed to be hydrophobic, the graphite/graphene surface also serves as a model system for many application-related studies. In the past, an ever-growing number of research groups have reported atomic force microscopy (AFM) experiments on the formation of well-ordered stripes on the graphite/graphene surface. Despite their ubiquitous appearance, the origin and many structural details of these stripes are still under debate. For example, the stripes have been reported to order in domains with different orientations with respect to each other. Moreover, different stripe widths ranging from 2 to 6 nm have been reported in literature. ,, Similarly, contradicting information is available on the solvation structure on top of the stripes. , Although some groups have ascribed the stripes to airborne contaminations or to the formation of methanol–water nanostructures, others have explained the origin of the stripes by intercalation and different interplanar stackings or the assembly of dissolved nitrogen molecules at the graphite/graphene–water interface. , The interpretation of the stripes being composed of nitrogen has received considerable attention because of its potential impact for explaining the long-range nature of the hydrophobic interaction. ,, In the view of this discussion, it becomes increasingly relevant to shed light onto the structural details of the stripes and, in particular, to clarify the chemical nature of the constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational SFG suggests itself as a tool because it has been successfully used to characterize water molecules at a range of aqueous interfaces, including air/water, alkane/water, and silica/water interfaces. The buried interface between an aqueous solution and an electrochemical material presents a considerable challenge, but graphene is a promising system here because it combines an atomically well-defined surface and IR transparency in the OH stretch region . Recent experimental results are encouraging: SFG spectra at an uncharged graphene/water interface have been measured, and a successful implementation in an electrochemical cell has been reported, although experimental challenges to prevent water intercalation between the substrate and graphene remain.…”
mentioning
confidence: 99%
“…The SPC/E potential was shown to provide an excellent description of water dynamics at ambient conditions. 6 In typical SFG experiments, 7 graphene is deposited on a solid substrate and can thus be approximated as immobile. The simulation box is periodically replicated in the two directions parallel to the graphene sheets.…”
mentioning
confidence: 99%
“…19 Additionally, surfacesensitive non-linear spectroscopies, second harmonic generation (SHG) and sum frequency generation (SFG), have been employed to provide insights into graphene's ability to screen or transmit interactions. [21][22][23][24][25][26][27][28] SHG results with water and SFG results with polystyrene on bare and graphene-coated silica suggest partial to complete opacity of graphene towards intermolecular interactions. 22,24,28 Similar conclusions can be derived from structure of ionic liquids on bare and graphene-coated CaF 2 and BaF 2 substrates, and water structure on bare and graphene-coated sapphire.…”
Section: Introductionmentioning
confidence: 97%
“…21,25,26 However, adsorption of 1-hexanol from cyclohexane on bare and graphene coated alumina, 23 and water structure on bare and graphene-coated CaF 2 and silica substrates indicated negligible effect of the graphene layer. 27 All these studies indirectly analyze the effect of graphene by comparing spectral signatures across bare and graphene-coated substrates. However, the strong dependence of SFG signals on orientation could influence the conclusions derived thereby necessitating the need for a direct molecular probe for resolving this ongoing debate over transparency of graphene.…”
Section: Introductionmentioning
confidence: 99%